Economic analysis of floating photovoltaic plants in Black Sea - Ioan-Cătălin Murărașu; Ioan Andrei Bulgaru; Alexandra Nedelcu (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2024)
Purpose: The main aim of the study was to estimate the levelized cost of electricity (LCOE) for a photovoltaic island project in the offshore area of Romania and the most effective possibilities to increase its profitability by reducing this indicator. Design/methodology/approach: The present study involves the analysis of the profitability of such an investment in the offshore area of Romania (considering CAPEX, OPEX, annual productivity and the levelized cost of energy), as well as the benefits it brings for the national energy system in periods of high deficit, such as those of drought or with low wind, and for the balancing activity in periods of instability. Findings: The LCOE for a floating photovoltaic park in the Romanian offshore area of the Black Sea can reach 211,303 euros/MWh, but this can be considerably reduced by increasing the installed capacity. This is due to the high costs of connecting to the terrestrial network. Also, costs can be reduced by combining the installed capacities of photovoltaic and wind energy production. Research limitations/implications: The main limitation of the research is that the possible discounts that can be obtained by an investor for the purchase of materials and their installation were not taken into account. Also, their prices can fluctuate considerably depending on the current realities of the international market. Originality/value: Photovoltaic plants are already one of the main renewable energy sources that Europeans rely on in the race to achieve the climate neutrality. In addition, in contrast to the wind farms, they are easier to manage and can even support the balancing of national energy systems, their production capacity being forecasted more easily. Since the main shortcoming of this source is the vast territory occupied by the installed panels, a solution already adopted worldwide is to install them on the surface of the inland waters or in offshore areas. Even if in these cases the installation and maintenance is more expensive, the land acquisition costs are lower or non-existent and the benefits for the environment are much more significant.
Keywords: O13; P18; P48; Q42; 330; Renewable energy; photovoltaic; offshore; Black Sea